Prevalence of high resilience in old age and association with perceived threat of COVID-19: results from a representative survey - Weitzel, Elena Caroline; Löbner, Margrit; Röhr, Susanne; Pabst, Alexander; Reininghaus, Ulrich; Riedel-Heller, Steffi Gerlinde (International journal of environmental research and public health, 2021)
Little is known about resilience in old age and its manifestation during the COVID-19 pandemic. This study aims to estimate the prevalence of high resilience in the German old age population. We further examine the socio-demographic correlates and whether high resilience reflects on older adults’ perception of the threat posed by COVID-19. The data were derived from a representative telephone survey of n = 1005 older adults (≥65 years) during the first COVID-19 lockdown. Assessments included socio-demographic variables, the perceived threat of COVID-19, and high resilience (Brief Resilience Scale; cutoff: ≥4.31). The association between high resilience and threat from COVID-19 was analyzed using ordinal logistic regression. The study sample had a mean age (SD) of 75.5 (7.1) years, and n = 566 (56.3%) were female. The estimated prevalence of high resilience was 18.7% (95% CI = [16.3; 21.2]). High resilience was more prevalent in the younger age group and participants with higher education levels. High resilience was significantly associated with a lower perception of threat from COVID-19. The results of the representative survey in the German old age population showed that one out of five adults aged 65 years and older had high resilience. Older adults with high resilience tended to feel less threatened by COVID-19. Further research on resilience in old age is needed to support vulnerable groups in the context of care.